Dispositivo de monitoreo de tiempos de fabricación de procesos de manufactura en línea en tiempo real - Cespedes Aguirre, Lourdes (2017)
The research work entitled “MONITORING TIME DEVICE MANUFACTURING ONLINE PROCESS IN REAL TIME “, is an experimental research, within the category of quasi-experimental and is based on the construction of a prototype, conducted according to standards of University Management Research of the National University Hermilio Valdizán Huánuco.  The overall objective of the research was to develop a prototype of monitoring time device manufacturing online process in real time, it was achieved through the fulfillment of the specific objectives, being the first of them, determining the electronic devices that will let detect the beginning and end of workstations of fabrication process and transmit the information to a communications center, for which assessment was put through to different types of devices that based on features that were considered to be optimal for the purpose, the microcontroller was chosen. The second specific objective set was to determine the configuration of the communications center that allows to capture and deliver data wirelessly from and to pre -defined stationary nodes. To fulfill this objective assessment underwent various types of wireless communication and then choose the Bluetooth and finally the third specific objective goal, formulated as, developing the software that simulates the production process that let interpret the data signals and transforms it into information for its monitoring and manufacturing times control in real time to the achievement underwent evaluation of different types of existing software in the market and based on the features that meet the requirements of the research was chosen Pure Basic. Finally we were able to develop the prototype with these three components, which has allowed to see the real time of each operation in a production process, wich results let determining minimum and maximum times of each cycle, the middle and the standard deviation, as well as identifying the bottlenecks in the production process, production rate, for decision making that will help to optimize the production process.